Nickel-ruthenium based ternary or higher alloys, products containing the same, and methods for producing and using the same
Nickel-ruthenium-based ternary alloys with specific compositions address the issues of high contact resistance and brittleness in existing probe materials by achieving high hardness and improved machinability, suitable for integrated circuit testing.
Patent Information
- Application Number
- JP2025520985
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-09
- Filing Date
- 2023-10-02
- Publication Date
- 2025-10-22
AI Technical Summary
Existing probe materials for testing integrated circuits, such as Paliney® H3C, Paliney® 7, and C17200, exhibit high contact resistance and brittleness, making them unsuitable for reliable electrical contact and machining, and conventional nickel-ruthenium alloys suffer from dendritic phases leading to inconsistent hardness.
Development of nickel-ruthenium-based ternary or higher alloys comprising specific weight percentages of nickel, ruthenium, and additional elements like gold, cobalt, chromium, etc., which are age-hardenable to achieve hardness exceeding 500 Knoop and exhibit a refined lamellar microstructure for improved mechanical properties.
The alloys provide enhanced hardness, reduced brittleness, and improved machinability, enabling reliable electrical contact and processing for probe applications in integrated circuit testing.
Smart Images

Figure 2025535107000001_ABST
Abstract
Description
[Technical Field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 63 / 415,348, filed October 12, 2022, and U.S. Provisional Patent Application No. 63 / 472,001, filed June 9, 2023, each of which is incorporated by reference herein in its entirety for all purposes. [Background technology]
[0002] Probes are often used to test integrated circuits at multiple points during manufacturing, including partially assembled on a wafer, completed on a wafer, and / or after packaging. Materials often used for such probes include Paliney® H3C (an alloy of silver, palladium, and copper), Paliney® 7 (an alloy of silver, palladium, copper, gold, platinum, and zinc), Paliney® 25 (an alloy of palladium, copper, silver, and rhenium), other palladium-silver-copper alloys, C17200 (a copper-beryllium alloy), C17500 (a copper-beryllium-cobalt alloy), C51000 (phosphor bronze), and W1 tool steel. Because copper- or iron-based materials produce high contact resistance when left bare, they are typically electroplated. In some cases, they may be first plated with a layer of nickel, followed by a layer of gold, gold-nickel, or gold-cobalt. In other instances, they may be plated with high-hardness electrodeposited palladium alloys such as palladium-nickel or palladium-cobalt. In exceptional cases, copper-based tips may be plated with rhodium. Summary of the Invention [Problem to be solved by the invention]
[0003] Features from any of the disclosed embodiments may be used in combination with each other without limitation. Additionally, other features and advantages of the present disclosure will become apparent to those skilled in the art upon consideration of the following detailed description and accompanying drawings.
[0004] In one embodiment, a nickel and ruthenium-based alloy is disclosed, the nickel and ruthenium-based alloy comprising about 48 to about 71 weight percent nickel, about 17 to about 45 weight percent ruthenium, and greater than 0 to about 20 weight percent of at least one ternary or higher addition, such as gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, tungsten, or any combination thereof.
[0005] In one embodiment, the nickel is present in an amount of about 54 to about 71 weight percent of the alloy.
[0006] In one embodiment, the nickel is present in an amount of about 50 to about 60% by weight of the alloy.
[0007] In one embodiment, the ruthenium is present in an amount of from about 27 to about 45 weight percent of the alloy.
[0008] In one embodiment, the ruthenium is present in an amount of about 25 to about 40% by weight of the alloy.
[0009] In one embodiment, the at least one tertiary or higher additive element is present in an amount of from about 0.1 to about 6 weight percent of the alloy.
[0010] In one embodiment, the at least one tertiary or higher additive element is present in an amount of from about 0.7 to about 11 weight percent of the alloy.
[0011] In one embodiment, the at least one tertiary or higher additive element is present in an amount of from about 1.4 to about 15 weight percent of the alloy.
[0012] In one embodiment, the at least one ternary or higher additive component comprises gold.
[0013] In one embodiment, the alloy is age hardened.
[0014] In one embodiment, the alloy exhibits a Knoop microhardness of about 500 or greater.
[0015] In one embodiment, the alloy exhibits a Knoop microhardness of about 600 or greater.
[0016] In one embodiment, the alloy exhibits an average lamellar wavelength of about 150 nm or less.
[0017] In one embodiment, a test probe or component of a test probe is disclosed that includes the nickel-ruthenium based alloy.
[0018] In one embodiment, the probe is configured as a cobra probe, a cantilever probe, a pogo pin probe, an LED probe, a vertical probe, or a MEMS probe.
[0019] In one embodiment, a probe card is disclosed that includes the test probes or components of the test probes described above.
[0020] In one embodiment, a method for producing a nickel-ruthenium based alloy is disclosed. The method includes forming the alloy. The alloy includes about 48 to about 71 weight percent nickel of the alloy, about 17 to about 45 weight percent ruthenium of the alloy, and greater than 0 to about 20 weight percent of at least one ternary or more additional element. The at least one ternary or more additional element includes gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, tungsten, or any combination thereof.
[0021] In one embodiment, the method further comprises homogenizing the alloy after forming the alloy.
[0022] In one embodiment, the method further comprises age hardening the alloy at a temperature of about 600 to about 1,300°C.
[0023] In one embodiment, the method further comprises forming the alloy into a desired shape before age hardening the alloy.
[0024] In one embodiment, the method further comprises age hardening the alloy at a temperature between about 700 and about 850°C. [Brief explanation of the drawings]
[0025] The drawings illustrate several implementations of the present disclosure, and the same reference numbers refer to the same or similar elements or features in different views or embodiments shown in the drawings. [Figure 1] FIG. 1 is a schematic illustration of the structural changes that occur in a homogeneous phase undergoing continuous precipitation (labeled "bulk diffusion") and discontinuous precipitation (labeled "interfacial diffusion") during age hardening. [Figure 2A] Figures 2A and 2B are images of Ni-Ru ternary alloys, Alloy 2189 and Alloy 2187, showing the dendritic microstructure of the as-cast alloys. [Figure 2B] Same as above [Figure 3] FIG. 3 is a graph showing the average lamellar wavelength of several Ni—Ru alloys, illustrating the relationship between aging temperature and average lamellar wavelength in Ni—Ru alloys. [Figure 4A] 4A and 4B are isometric and cross-sectional views of a pogo pin according to an embodiment of the present disclosure. [Figure 4B] Same as above [Figure 5] FIG. 5 is an isometric view of an LED probe according to an embodiment of the present disclosure. [Figure 6A] 6A and 6B show Table 1. [Figure 6B] Same as above [Figure 7A] 7A and 7B show Table 2. [Figure 7B] Same as above [Figure 8A] FIG. 8A is a graph showing the hardness of various Ni—Ru binary alloys to determine the effect of ruthenium on a homogenized nickel-rich matrix. [Figure 8B] FIG. 8B is a graph showing the hardness of each Ni—Ru alloy after the homogenization treatment. [Figure 9A] 9A-9D are images obtained from alloy 2236, alloy 2148, alloy 2179, and alloy 2147, respectively, showing the various wavelengths of their discontinuously precipitated microcomponents. [Figure 9B] Same as above [Figure 9C] Same as above [Figure 9D] Same as above [Figure 10] FIG. 10 is a graph showing the relationship between the measured hardness and the measured mean lamellar wavelength of the Ni—Ru alloys after age hardening obtained from Table 2. [Figure 11] FIG. 11 is a ternary phase diagram showing the hardness of nickel-ruthenium alloys in terms of Knoop hardness. [Figure 12] FIG. 12 is a graph showing the effect of a gold ternary addition to a nickel-ruthenium matrix after age hardening. DETAILED DESCRIPTION OF THE INVENTION
[0026] Nickel-ruthenium-based ternary or higher alloys, products, and methods of making and using them are disclosed herein. An exemplary nickel-ruthenium-based ternary or higher alloy ("Ni-Ru ternary or higher alloy") comprises about 48 to about 71 weight percent ("wt %) nickel of the alloy, about 17 to about 45 weight percent ruthenium of the alloy, and about 0.1 to about 20 weight percent of at least one ternary or higher alloy element. The ternary or higher alloy element may comprise gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, tungsten, or any combination thereof. The Ni-Ru ternary and higher alloys may be age hardenable and may exhibit hardnesses of greater than 500 Knoop ("HK") after age hardening. The alloys may be used in electronic test probe applications.
[0027] Ni—Ru ternary or higher alloys may be processable and formable. The alloys may be age-hardenable. After age-hardening, the alloys may exhibit mechanical properties with unexpectedly high Knoop hardness levels exceeding 500 Knoop hardness ("HK"), and in some embodiments, exceeding 600 HK. Unless otherwise specified herein, "hardness" refers to the average microhardness of the Ni—Ru ternary or higher alloy. The hardness of Ni—Ru ternary or higher alloys may be measured using any suitable technique, such as by testing polished sections (e.g., having a surface roughness of about 1 μm RMS) of the Ni—Ru ternary or higher alloy. The Ni—Ru ternary or higher alloys may be ternary alloys (e.g., Ni—Ru-X), quaternary alloys (e.g., Ni—Ru-X1-X2), etc.
[0028] The Ni-Ru ternary or higher alloys disclosed herein have been found to be an improvement over nickel-ruthenium binary and ternary alloys having compositions different from those of the Ni-Ru ternary or higher alloys disclosed herein. For example, nickel-ruthenium binary alloys have been found to exhibit an age-hardened hardness of about 360 on the Vickers scale (about 365 HK). In another example, nickel-ruthenium ternary alloys containing zirconium or titanium have been found to form extremely brittle and difficult-to-machine alloys. However, the Ni-Ru ternary or higher alloys disclosed herein exhibit significantly greater hardness than nickel-ruthenium binary alloys, and are less brittle and more machineable than nickel-ruthenium ternary alloys containing zirconium or titanium. In another example, conventional nickel-ruthenium-platinum alloys are disclosed in Glaner (Glaner L, A study of Ni-Pt-Ru and Co-Pt-Ru systems, University of Witzerland (2009)). The nickel-ruthenium-platinum alloys explicitly discussed in Glaner do not appear to be within the scope of the Ni-Ru ternary or higher alloys disclosed herein. Glaner's nickel-ruthenium-platinum alloys exhibit two dendritic phases that cause the alloys to exhibit regions of high and low hardness. Furthermore, Glaner's nickel-ruthenium-platinum alloys are not homogenized, but instead annealed. Therefore, Glaner's nickel-ruthenium-platinum alloys do not exhibit the optimized hardness of the Ni-Ru ternary or higher alloys disclosed herein. For example, the hardness of Glaner's nickel-ruthenium-platinum alloys depends on the hardness of their secondary phases, while the hardness of the Ni-Ru ternary or higher alloys disclosed herein depends, in part, on the high interface density provided by fine lamellae and optimal thermal practices. In another example, U.S. Pat. No. 2,105,312 ("the '312 patent") discloses palladium-based nickel-ruthenium-platinum alloys that are not within the scope of the Ni-Ru ternary or higher alloys disclosed herein.The nickel-ruthenium-platinum alloys of the '312 patent use nickel and ruthenium to harden palladium, whereas the Ni-Ru ternary or higher alloys disclosed herein are nickel-based alloys that use, in part, the nickel / ruthenium interface to harden the alloy and the ternary or higher additions, thereby modifying the kinetics of the Ni-Ru ternary or higher alloys and improving their nobility (e.g., making them less susceptible to oxidation, corrosion, etc.).
[0029] As described in more detail below, the Ni-Ru ternary and higher alloys disclosed herein can be age-hardened. Generally, two types of age-hardening precipitation reactions are common in concentrated metallic solid solutions: continuous precipitation ("CP") and discontinuous precipitation ("DP"). Figure 1 is a schematic diagram illustrating the structural changes that occur in a homogeneous phase undergoing CP (labeled "bulk diffusion") and DP (labeled "interface diffusion") during age hardening. In CP, bulk diffusion dominates, resulting in overall precipitation at heterogeneous and homogeneous nucleation sites. As time progresses, solutes in the matrix precipitate from solution, and the composition "continuously" evolves to an equilibrium composition. DP manifests differently because it is dominated by interfacial diffusion and can only form on heterogeneous nucleation sites. As colonies nucleate, a reaction front advances into the matrix, providing an easy diffusion path for atoms. The evolution from α → α' + β occurs suddenly, locally, and "discontinuously." The DP reaction is sometimes called "decomposition" of the α-phase, and the retained α-phase is sometimes called "undecomposed."
[0030] DP produces a lamellar microstructure of alternating "plates" instead of the more common grain shape associated with precipitation. The spacing between these "plates" creates additional interfaces that hinder dislocation motion and, consequently, improve hardness. While CP reactions are generally considered to be inherently finer than DP reactions, only alloy 2288 (see Table 1) exhibited CP. The resulting Widmanstatten plates formed after prolonged exposure to 900°C and lacked facile heterogeneous nucleation sites. The slow reaction rate does not promote the formation of ultrafine precipitates. The lamellar microstructure appears and behaves similarly to eutectoid decomposition in other systems (e.g., iron-silicon-germanium, Paliney® 7, pearlitic steel, copper-aluminum, etc.). DP was observed in the Ni-rich region of the Ni-Ru binary system, but the resulting Vickers hardness was only approximately 360 HV.
[0031] Nickel can form about 48 to about 71 weight percent of the Ni—Ru ternary or polymeric alloys disclosed herein, e.g., in the range of about 54 to about 71 weight percent, about 50 to about 60 weight percent, about 48 to about 52.5 weight percent, about 50 to about 55 weight percent, about 52.5 to about 57.5 weight percent, about 55 to about 60 weight percent, about 57.5 to about 62.5 weight percent, about 60 to about 65 weight percent, about 62.5 to about 67.5 weight percent, or about 65 to about 70 weight percent. The amount (i.e., weight percent) of nickel present in the Ni—Ru ternary or higher multi-component alloys disclosed herein can be selected based on several factors. In one example, it has been found that the forgeability of the alloy depends in part on the amount of nickel present in the Ni—Ru ternary or higher multi-component alloy. In particular, it has been found that increasing the amount of nickel in an alloy generally makes the Ni-Ru ternary or higher alloy more forgeable, and vice versa. Therefore, the amount of nickel in a Ni-Ru ternary or higher alloy may be selected based on the desired wroughtability of the alloy. In one example, the amount of nickel in a Ni-Ru ternary or higher alloy may depend on the ternary or higher additives present in the alloy. For example, some ternary or higher additives may have a tendency to form nickel-rich or ruthenium-rich particles, which may adversely affect the properties of the Ni-Ru ternary or higher alloy. In such an example, the amount of nickel may be increased if the ternary or higher additive has a tendency to form solute-rich particles and / or if the ternary or higher additive has a tendency to form ruthenium-rich particles. In one example, the amount of nickel in a Ni-Ru alloy may be selected based on the desired amount of ruthenium and the ternary or higher additives in the Ni-Ru ternary or higher alloy, for reasons explained in more detail below.
[0032] Ruthenium may comprise about 17 to about 45 wt. % of the Ni—Ru ternary or higher alloys disclosed herein, e.g., about 27 to about 45 wt. %, about 25 to about 40 wt. %, about 17.5 to about 22.5 wt. %, about 20 to about 25 wt. %, about 22.5 to about 27.5 wt. %, about 25 to about 30 wt. %, about 27.5 to about 32.5 wt. %, about 30 to about 35 wt. %, about 32.5 to about 37.5 wt. %, about 35 to about 40 wt. %, about 37.5 to about 42.5 wt. %, or about 40 to about 45 wt. The amount of ruthenium present in the Ni—Ru ternary or higher alloys disclosed herein can be selected based on several factors. In one example, it has been found that the average lamellar wavelength produced by DP depends in part on the amount of ruthenium present in the Ni—Ru ternary or higher alloy. In particular, increasing the amount of ruthenium in a Ni-Ru or higher ternary alloy decreases the average lamellar wavelength of the Ni-Ru or higher ternary alloy and lowers the aging temperature (by increasing the decomposition rate), and vice versa. Therefore, the amount of ruthenium present in a Ni-Ru or higher ternary alloy can be selected based on the desired average lamellar wavelength of the Ni-Ru or higher ternary alloy. The hardness of a Ni-Ru or higher ternary alloy depends in part on the average lamellar wavelength (i.e., decreasing the average lamellar wavelength increases the hardness of the Ni-Ru or higher ternary alloy, and vice versa), and therefore, the amount of ruthenium in a Ni-Ru or higher ternary alloy can be selected based on the desired hardness of the Ni-Ru or higher ternary alloy. In one example, it has been found that increasing the amount of ruthenium in a Ni-Ru or higher ternary alloy increases the reaction front velocity at any given temperature. Therefore, the amount of ruthenium in a Ni-Ru or higher ternary alloy can be selected based on the desired average lamellar wavelength. In one example, the amount of ruthenium can be selected based on the desired solid solution strength of the Ni—Ru ternary or higher alloy, as it has been found that increasing the amount of ruthenium in the Ni—Ru ternary or higher alloy increases the solid solution strength of the Ni—Ru ternary or higher alloy, and vice versa.In one example, the amount of ruthenium in a Ni-Ru ternary or higher alloy may be selected based on the desired forging process, since it has been found that decreasing the amount of ruthenium in the Ni-Ru ternary or higher alloy makes the Ni-Ru ternary or higher alloy more forgeable. In one example, the amount of ruthenium in a Ni-Ru ternary or higher alloy may be selected based on the desired homogenization temperature, since it has been found that decreasing the amount of ruthenium in a Ni-Ru ternary or higher alloy allows for a decrease in the homogenization temperature, and vice versa. In one example, the amount of ruthenium in a Ni-Ru ternary or higher alloy may be selected based on the desired amount of nickel and the amount of the ternary or higher added components in the Ni-Ru ternary or higher alloy.
[0033] The content of the third or more additional components is greater than zero, for example, about 0.08 to about 6 wt%, about 0.7 to about 11 wt%, about 1.4 to about 15 wt%, about 0.01 to about 0.05 wt%, about 0.05 to about 0.08 wt%, about 0.05 to about 0.1 wt%, about 0.08 to about 0.15 wt%, about 0.1 to about 0.2 wt%, about 0.15 to about 0.25 wt%, about 0.2 to about 0.3 wt%, about 0.25 wt% to about 0.4 wt%, about 0.3 to about 0.5 wt%, about 0.4 to about 0.75 wt%, about 0.5 to about 1 wt%, about 0.7 The amount of the ternary or higher additive component may be in the range of 5 to about 1.25 wt%, about 1 to about 1.5 wt%, about 1.25 to about 1.75 wt%, about 1.5 to about 2 wt%, about 1.75 to about 2.5 wt%, about 2 to about 3 wt%, about 2.5 to about 3.5 wt%, about 3 to about 4 wt%, about 3.5 to about 4.5 wt%, about 4 to about 5 wt%, about 4.5 to about 6 wt%, about 5 to about 7 wt%, about 6 to about 8 wt%, about 7 to about 9 wt%, about 8 to about 10 wt%, about 9 to about 12 wt%, about 10 to about 14 wt%, about 13 to about 17 wt%, or about 16 to about 20 wt%. The amount of the ternary or higher additive component may be selected based on several factors. In one example, the amount of the ternary or higher additive component may depend on the specific elements forming the ternary or higher additive component. In one example, the amount of the ternary or higher element may depend on the amount of nickel and the amount of ruthenium in the Ni-Ru ternary or higher element multi-component alloy, as well as whether the ternary or higher element has a tendency to form nickel-rich or ruthenium-rich particles. However, it should be noted that the amount of the ternary or higher element may generally be selected to be about 0.08 wt.% or greater. Generally, the effect of the ternary or higher element on the Ni-Ru ternary or higher element multi-component alloy increases exponentially, and even low concentrations show measurable improvements in microhardness. In one example, as shown in FIG. 12, adding 0.08% of the ternary or higher element may increase the hardness of the Ni-Ru ternary or higher element multi-component alloy by about 10%. Ternary or higher elements may have a significant effect on the hardness of the Ni-Ru ternary or higher element multi-component alloy. For example, it is believed that when a ternary or higher element is added to form about 0.5 wt. % of the Ni—Ru ternary or higher alloy, the hardness of some of the Ni—Ru ternary or higher alloy compositions disclosed herein may be increased by more than 100 HK compared to a substantially similar nickel-ruthenium binary alloy.Similarly, it is believed that ternary or higher additions forming about 0.25 wt.% of the Ni—Ru ternary or higher alloys may be responsible for some of the Ni—Ru ternary or higher alloys disclosed herein exhibiting hardnesses in excess of 650 HK. It is also noted that amounts of ternary or higher additions greater than about 20 wt.% generally adversely affect the Ni—Ru ternary or higher alloys, such as by forming ternary or higher addition-rich grain boundary decoration, and therefore the amount of ternary or higher additions is generally selected to be less than about 20 wt.%.
[0034] Ternary or higher addition elements have at least some solubility difference from nickel and / or ruthenium, which may cause Ni-Ru ternary or higher alloys to exhibit beneficial properties. As previously mentioned, the ternary or higher addition elements may include one or more of gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, or tungsten.
[0035] Ternary and higher additions may include platinum, as it has been found that the amount of platinum in Ni-Ru ternary or higher alloys can be used to control whether the age hardening process results in complete decomposition or partial decomposition consisting of decomposed phases along the grain boundaries and undecomposed grain centers. For example, selecting the amount of platinum in a Ni—Ru ternary or higher alloy to be less than 10 wt.%, more specifically less than 7 wt.%, may result in complete decomposition of the Ni—Ru ternary or higher alloy during age hardening at certain Ni—Ru ternary or higher alloy compositions and certain age hardening processes. On the other hand, increasing the amount of platinum in a Ni—Ru ternary or higher alloy to more than 7 wt.%, more specifically more than 10 wt.%, may result in only partial decomposition of the Ni—Ru ternary or higher alloy during age hardening at certain Ni—Ru ternary or higher alloy compositions and certain age hardening processes. Platinum (and other noble metals) may also increase the noble character of a Ni—Ru ternary or higher alloy.
[0036] Rhenium has low solubility in nickel and high affinity for ruthenium. Thus, for example, when the amount of rhenium in a Ni-Ru or higher ternary alloy exceeds 9 wt. % in a particular Ni-Ru or higher ternary alloy composition, rhenium may form large, insoluble ruthenium-rich particles. Surprisingly, the insoluble ruthenium-rich particles do not adversely affect the workability of the Ni-Ru or higher ternary alloy. The insoluble ruthenium-rich particles can be used to reduce the volume fraction of the lamellar microstructure by providing heterogeneous nucleation sites that promote uncoupled DP. Therefore, the amount of rhenium can be used to control the lamellar microstructure and, therefore, the hardness of the Ni-Ru or higher ternary alloy. It should be noted that when rhenium is present in amounts less than 9 wt. % and / or in certain compositions of Ni—Ru ternary or higher alloys (e.g., Ni—Ru ternary or higher alloys containing at or near 17 wt. % ruthenium), rhenium may form insoluble ruthenium-rich particles.
[0037] The ternary or higher additive elements may include at least one of tungsten, molybdenum, tantalum, or niobium. The ternary or higher additive elements of tungsten, molybdenum, tantalum, and niobium can improve the high-temperature stability (e.g., creep resistance) of Ni-Ru ternary or higher alloys. Tungsten, molybdenum, tantalum, and niobium have been found to affect the colony growth and decomposition of Ni-Ru ternary or higher alloys. Therefore, the composition of the Ni-Ru-x alloy (i.e., the amount of nickel, ruthenium, and ternary or higher additive elements in the Ni-Ru ternary or higher alloy), the homogenization conditions, and the age-hardening conditions can be selected to favorably counteract the adverse effects of tungsten, molybdenum, tantalum, and / or niobium on the colony growth and decomposition of Ni-Ru ternary or higher alloys. Furthermore, it should be noted that selecting a relatively low amount of niobium (e.g., less than 1.5 wt.%) may make the Ni—Ru ternary or higher alloy difficult to melt and cast. Thus, in some instances, the amount of niobium in the Ni—Ru ternary or higher alloy may be selected to be greater than 1.5 wt.%. It should be noted that the Ni—Ru ternary or higher alloy may contain less than 1.5 wt.% if it is formed using certain processing parameters and / or if the Ni—Ru ternary or higher alloy contains one or more additional ternary or higher elements in addition to niobium.
[0038] In one embodiment, the ternary or higher additive component can include palladium. Palladium as a ternary or higher additive component can prevent or at least inhibit the formation of a pseudoeutectic phase, thereby increasing the noble metal character of the Ni—Ru or higher ternary alloy. Palladium has been found to affect the melting of the Ni—Ru or higher ternary alloy during homogenization, the formation of grain boundaries with nickel pseudoeutectic phases, and the formation of pores. Therefore, the composition and homogenization conditions of the Ni—Ru or higher ternary alloy containing palladium can be selected so that palladium has a beneficial effect at the expense of its adverse effects on the melting of the Ni—Ru or higher ternary alloy during homogenization, the formation of grain boundaries with nickel pseudoeutectic phases, and the formation of pores. For example, some compositions of Ni-Ru ternary or higher alloys containing palladium formed using homogenization treatments exhibiting temperatures exceeding 1400°C induce non-equilibrium melting of the Ni-Ru ternary or higher alloy during the homogenization heat treatment, resulting in significant grain boundary decoration with a palladium-nickel pseudoeutectic phase and the formation of pores. Thus, for example, the homogenization heat treatment can be selected to include heating the Ni-Ru ternary or higher alloy containing palladium to a temperature less than 1400°C (e.g., about 1200°C).
[0039] Tertiary or higher additions may include rhodium, as it has been found to enable rapid colony growth and at least partial (e.g., complete) decomposition during age hardening. Furthermore, rhodium can detrimentally cause the formation of coarse lamellae and equiaxed grains upon overaging.
[0040] Ternary or higher additive elements may include gold. Gold is miscible with nickel at high temperatures, immiscible with nickel at low temperatures, and immiscible with ruthenium. Furthermore, gold may effectively refine the lamellar structure, increase the reaction front velocity, promote rapid decomposition of Ni-Ru ternary or higher alloys during age hardening, and generate heterogeneous nucleation sites within the alloy particles. For example, gold has been observed to promote the formation of a fine lamellar structure in Ni-Ru ternary or higher alloys during age hardening at approximately 700°C. Gold may also make Ni-Ru ternary or higher alloys highly workable. Note that Ni-Ru ternary or higher alloys containing large amounts of gold and ruthenium may cause the formation of ruthenium-rich and gold-rich microcomponents, which may inhibit complete homogenization of the Ni-Ru ternary or higher alloy at 1400°C. For example, alloys 2288, 2289, 2248, 2247, and 2294 exhibited ruthenium-rich and gold-rich trace elements. For ease of illustration, the compositions of alloys 2288, 2289, 2248, 2247, and 2294 are provided in Table 1 in Figures 6A and 6B. The mutual immiscibility of ruthenium and gold in the nickel matrix results in solid solubility competition. For example, increasing the ruthenium concentration decreases the solubility of gold, and increasing the gold concentration decreases the solubility of ruthenium. Saturation and the formation of gold-rich and ruthenium-rich regions occur at 1.5 wt% Au in alloy 2248-based alloys, 3 wt% Au in alloy 2179-based alloys, and 5.5 wt% Au in alloy 2147-based alloys. Surprisingly, however, it was found that large amounts of gold and ruthenium do not adversely affect the workability of Ni-Ru ternary and higher alloys. The compositions of alloys 2248, 2179, and 2147 are provided in Table 1 in Figures 6A and 6B. It should be noted that even low concentrations of gold can have a significant effect on the age-hardened microhardness of Ni-Ru ternary or higher alloys. For example, as shown in Figure 12, the addition of 0.08 wt.% gold to a Ni-Ru ternary or higher alloy based on alloy 2147 increases the age-hardened microhardness from about 400 HK to about 450 HK, demonstrating that even low concentrations of gold have a significant effect on the microhardness of Ni-Ru ternary or higher alloys.
[0041] The ternary or higher additive element may include cobalt and / or iridium. Cobalt and iridium exhibit high solubility in both nickel and ruthenium. It has been found that cobalt and iridium can promote homogenization of Ni-Ru ternary or higher alloys without releasing ruthenium or forming precipitates. It has also been found that Ni-Ru ternary or higher alloys containing cobalt and / or iridium exhibit good workability. Furthermore, it has been found that a relatively large amount of cobalt in a Ni-Ru ternary or higher alloy (e.g., cobalt forms about 12 wt. % or more of the Ni-Ru ternary or higher alloy) can form a blue oxide layer on the alloy, making the alloy magnetic after age hardening.
[0042] In one embodiment, the ternary or higher element addition may include chromium. Chromium has been found to affect the microstructure by increasing the volume fraction of the Ru-rich phase during homogenization, thereby increasing the population of heterogeneous nucleation sites. Therefore, the composition (e.g., amounts of nickel, ruthenium, and chromium) and homogenization treatment of a Ni-Ru ternary or higher alloy may be selected to favorably offset the adverse effects of chromium on the microstructure and population of heterogeneous nucleation sites. For example, certain compositions of Ni-Ru ternary or higher alloys containing nickel may undergo certain homogenization treatments to result in the appearance of ruthenium-rich regions in the as-cast microstructure, which may then coarsen into a mesoscale dual-phase microstructure.
[0043] In one embodiment, the ternary or higher element addition may include vanadium. Vanadium has been found to promote decomposition of Ni-Ru ternary or higher alloys during age hardening, although it impairs workability. Furthermore, vanadium may cause some melting of Ni-Ru ternary or higher alloys during homogenization, which involves temperatures of approximately 1400°C. Surprisingly, it has been found that such melting does not adversely affect the workability of the alloy.
[0044] Ternary or higher additive elements may include copper. Copper can improve the workability of Ni-Ru ternary or higher alloys and refine the lamellar structure of the alloy after age hardening. It should be noted that certain compositions of Ni-Ru ternary or higher alloys containing copper may melt during homogenization and form coarse grains upon solidification. However, it has surprisingly been found that Ni-Ru ternary or higher alloys containing coarse grains remain workable. Furthermore, copper, like gold, can increase the microhardness of Ni-Ru ternary or higher alloys.
[0045] As discussed above, Ni—Ru ternary or higher alloys may contain two or more ternary or higher additive elements. The two or more ternary or higher additive elements may enable the Ni—Ru ternary or higher alloy to exhibit the respective advantages of the two or more ternary or higher additive elements. For example, a Ni—Ru ternary or higher alloy containing both gold and platinum may exhibit the advantages of gold (e.g., efficient refinement of the lamellar structure) and platinum (e.g., increased noble metal character of the alloy).
[0046] The Ni—Ru ternary or higher alloy may be free or substantially free of one or more elements. In one example, the Ni—Ru ternary or higher alloy may be free or substantially free of lead, mercury, and cadmium. In one example, the alloy may be free or substantially free of zirconium, since zirconium can form zirconium-rich precipitates that interfere with or prevent the workability of the Ni—Ru ternary or higher alloy. In one example, the alloy may be substantially free of titanium, since titanium forms an undesirable low-melting eutectic trace element that easily oxidizes the Ni—Ru alloy. In one embodiment, the alloy may be free or substantially free of carbon or silicon. In one example, the alloy may be free of iron or zirconium. In one example, the alloy may be free or substantially free of any one or more of the ternary or higher additive elements disclosed herein. For example, some ternary additions interact adversely with one another, some ternary additions (e.g., niobium) are deleterious at low concentrations, and / or maintaining ternary or higher additions below a desired amount may require omitting at least one ternary addition. Note that "substantially free" encompasses trace amounts (e.g., about 0.6 wt. % or less, about 0.4 wt. % or less, or about 0.2 wt. % or less) of elements that do not affect the material properties of the alloy.
[0047] The Ni—Ru ternary or higher alloy may contain one or more impurities forming less than or equal to about 0.6 wt. %, less than or equal to about 0.4 wt. %, or less than or equal to about 0.2 wt. %.
[0048] In one embodiment, the Ni—Ru ternary or higher alloy may include elements in addition to nickel, ruthenium, a tertiary or higher additive, and optionally one or more impurities and / or structurally insignificant oxide layers. Such elements may include iron, rhodium, osmium, platinum, iridium, cobalt, copper, or sulfur. In one embodiment, the Ni—Ru alloy may include only nickel, ruthenium, one or more ternary or higher additives disclosed herein, and optionally one or more impurities and / or structurally insignificant oxide layers.
[0049] The Ni-Ru ternary or higher alloy can be formed using any suitable technique. In one embodiment, the alloy can be formed by mixing and alloying the individual elements together. For example, the alloy can be formed by mixing nickel, ruthenium, and a tertiary or higher additive component together in either their elemental and / or precursor forms. The method can include mixing the nickel, ruthenium, and the tertiary or higher additive component together, and then alloying the nickel, ruthenium, and the tertiary or higher additive component together using any suitable technique, such as casting.
[0050] It has been found that Ni—Ru ternary or higher alloys can contain at least one of numerous cored Ru-rich or Ni-rich dendrites, microsegregation (compositional changes due to solidification), or particles with different crystal structures that may be detrimental to processing in some configurations. Depending on the concentrations and elements present in each Ni—Ru ternary or higher alloy, numerous cored Ru-rich or Ni-rich dendrites may be the predominant microcomponent of the as-cast alloy. For example, Figures 2A and 2B are images of alloys 2189 and 2187, respectively, showing the dendritic microstructure of the as-cast alloys. The compositions of alloys 2189 and 2187 are listed in Table 1 (provided in Figure 6A) and are discussed in more detail in the Examples. In some embodiments, the Ni—Ru ternary or higher alloys can be subjected to a homogenization treatment after formation of the Ni—Ru alloy so that the Ni—Ru ternary or higher alloy exhibits a single phase (e.g., face-centered cubic phase). The homogenization treatment can include heating the Ni—Ru ternary or higher alloy to a temperature above about 900°C, e.g., above about 1000°C, or in the range of about 900°C to about 1100°C, about 1000°C to about 1200°C, about 1100°C to about 1300°C, about 1200°C to about 1400°C, about 1300°C to about 1500°C, or about 1400°C to about 1550°C. The homogenization step can be carried out in a reducing atmosphere (e.g., an atmosphere with −3.5% H), an inert atmosphere, or any other suitable atmosphere. The hardness of the Ni—Ru ternary or higher alloy after homogenization has been found to be substantially similar to the hardness of a substantially similar nickel-ruthenium binary alloy.
[0051] The Ni—Ru ternary or higher alloys can be processed and / or shaped after forming the Ni—Ru ternary or higher alloy (e.g., after homogenization). For example, the alloys can be processed and / or shaped into any of the probes disclosed below, plates, rods, wires, or any other suitable shape. Because it is expected that processing and / or shaping of the alloys can best be produced from Ni—Ru ternary or higher alloys having a microhardness of less than about 500 HK, the alloys can be processed and / or shaped before age hardening.
[0052] In some embodiments, Ni—Ru ternary or higher alloys can be age-hardened, for example, after homogenization. As discussed above, age-hardening of the alloys can be caused, at least in part, by DP reactions that form lamellar structures. For example, the average lamellar wavelength and resulting phase boundary density are expected to contribute to the resulting hardness of Ni—Ru—X alloys. While not wishing to be bound by any particular theory, the hardness of Ni—Ru ternary or higher alloys can be governed by the Hall-Petch relationship, which states that strength increases with decreasing grain, phase, and / or lamellar length scales.
[0053] The age-hardening process may involve heating the Ni-Ru ternary or higher alloy to temperatures above 600°C, e.g., in the range of about 600 to about 800°C, about 700 to about 900°C, about 800 to about 1000°C, about 900 to about 1100°C, about 1000 to about 1200°C, or about 1100 to about 1300°C. Ni-Ru ternary or higher alloys have been found to exhibit an approximately exponential relationship between aging temperature and the average lamellar wavelength in the decomposed minor constituents. Figure 3 is a graph illustrating the lamellar wavelength of several Ni-Ru binary and ternary alloys (the compositions of these Ni-Ru alloys are shown in Table 1 in Figures 6A and 6B and discussed in more detail with respect to the Examples), demonstrating the relationship between aging temperature and the average lamellar wavelength in Ni-Ru binary or higher alloys. It has also been found that increasing the ruthenium concentration in Ni-Ru alloys reduces the mean lamellar wavelength and increases the reaction front velocity at low temperatures. It should be noted that there is a diminishing return on shortening the mean lamellar wavelength via aging parameters. For example, the mean lamellar wavelength for a given ruthenium concentration may be limited by slow growth rates below about 600°C and slow nucleation rates above about 1300°C. The exact temperature at which DP occurs may vary based on the alloy composition. It has also been found that aging Ni-Ru ternary or higher alloys below the nickel-ruthenium solvus temperature does not guarantee decomposition by itself.
[0054] In some embodiments, the Ni-Ru ternary or higher alloys disclosed herein can form probes, such as those used to test integrated circuits. Such probes can test integrated circuits at multiple points during manufacturing. Different methods exist for contacting test pads on these devices under test (DUTs). Probes come in a myriad of configurations, with several important types including vertical probes, buckling beam probes, pogo pin probes, cobra probes, cantilever probes, microelectromechanical systems (MEMS) probes, and light-emitting diode (LED) probes. In one embodiment, the probes may form part of a probe card.
[0055] Pogo pins are used for testing and programming semiconductor devices. Other applications of pogo pins include contact in flip-chip packaging, where pogo pins have superior probe mark position control compared to vertical or cantilever probes. FIGS. 4A and 4B are isometric and cross-sectional views of a pogo pin 400 according to one embodiment. The pogo pin 400 functions as a compliant connection structure providing electrical continuity between a proximal contact point 401 and a distal contact point 402. The pogo pin 400 includes a plunger 403 configured to press against the proximal contact point 401. The resultant force depresses a spring 404 inside the body 405 of the pogo pin 400. The spring 404 provides the necessary contact force to ensure electrical contact between the proximal contact point 401 and the probe plunger 403, and between the distal contact point 402 and the probe tip 406. The body 405 of the pogo pin 400 may include bronze, brass, or a high-copper alloy. The body 405 may be plated first with nickel and second with gold. The spring 404 may be mild steel, stainless steel, or a high copper alloy. Generally, the distal contact point 402 mates with a metal test point on the device under test ("DUT").
[0056] The pogo pin 400 may use an aggressive wedge, crown, or castle tip on the distal contact point 402 to engage the solder bump. The tip 406 of the pogo pin 400 generally serves multiple simultaneous functions: maintain low contact resistance, have bulk conductivity, minimize material adhesion from the DUT, and resist dulling of sharp features due to abrasive cleaning (e.g., abrasive cleaning of the tip 406 may be necessary approximately every 200-2,000 touchdowns to remove adhered metal from the DUT). By forming the tip 406 from a Ni-Ru ternary or higher alloy, the tip 406 of the pogo pin 400 is able to exhibit each of these functions, in part, because the Ni-Ru ternary or higher alloy exhibits a hardness of greater than 500 HK.
[0057] As previously mentioned, another probe that can include a Ni-Ru ternary or higher alloy is an LED probe. The LED probe can include an LED, mini-LED, micro-LED, or photodiode. At the wafer-through-package die level, test pads on the DUT can be contacted by a set of LED probes, resulting in the diode being energized and the emitted light being collected and quantified. Figure 5 shows an isometric view of an LED probe 500 according to one embodiment. The LED probe 500 can include a wire 501 having a diameter of about 50 to about 750 μm (e.g., about 50 to about 100 μm or about 250 to about 750 μm). The LED probe 500 also includes a distal tip 502 configured to contact the DUT ground at an acute angle, a body 503 including a portion that functions as a cantilever spring, and a proximal end 504 configured for fastening to the head of a photonic tester.
[0058] Periodic abrasive cleaning may be required to clean the tip 502 of the LED probe 500 of any foreign matter that may cause high contract resistance. The cleaning process imposes a small amount of material removal on the tip 502 of the LED probe 500, thus further dulling the probe tip 502 with each cleaning cycle. The tip 502 of the LED probe 500 may be formed from a Ni—Ru alloy because this alloy is relatively hard and resists wear on the tip 502 during cleaning. [Example]
[0059] Comparative Examples and Examples Several comparative examples (labeled Alloy 2147, Alloy 2148, Alloy 2179, CE-1, and CE-2) and examples were produced by casting. The compositions of each of the comparative examples and examples are listed in Table 1. Table 1 is provided in Figures 6A and 6B. The alloys were homogenized at 1400°C in a weakly reducing atmosphere of N containing 3.5% H2 and then age-hardened at 700°C for 2 hours. Table 2 lists the physical properties of the comparative examples and examples of various Ni-Ru binary or higher alloys. For ease of explanation, Table 2 is provided in Figures 7A and 7B. The hardness of some of the comparative examples and examples listed in Table 2 was measured after homogenization and age-hardening treatment.
[0060] The hardness of the comparative examples and examples was measured using a LECO M-400 hardness tester. To measure hardness, sections were taken from each of the listed alloy compositions. The sections were mounted in resin and polished using 1 μm polishing media. The hardness tester included a thin, pyramidal-shaped probe with a diamond tip that pressed a 100-gram force load into the prepared material surface. When the probe was withdrawn, the indentation made by the probe on the surface was measured. To ensure reliability, five indentations were measured randomly, and the average value was reported.
[0061] Note that, as identified in Table 2, some alloys did not respond to the age-hardening heat treatment or responded at a low volume fraction, so the hardness of some of the comparative examples and examples was not measured. For example, Table 2 lists the hardness of some of the comparative examples and examples as A, B, C, or D. A indicates that the age-hardening response was irregular or absent, B indicates that the volume of the aged microstructure was insufficient for microhardness measurement, C indicates that hardness was not measured due to poor workability, and D indicates that hardness was not measured. Note that alloys with hardness ratings of A, B, or C do not indicate that the alloy is not viable, but merely that one or more problems occurred during processing that prevented the alloy's hardness from being measured. It is believed that alloys with hardness ratings of A, B, or C may still be viable by optimizing, for example, the alloy's composition, the homogenization treatment used to form the alloy, or the aging process used to form the alloy.
[0062] The average lamellar wavelengths for each of the comparative examples and examples were measured after age-hardening treatment, unless otherwise specified in Table 2. The average lamellar wavelengths were determined from scanning electron microscope images using ImageJ and Matlab. The region with the shortest observed wavelength (meaning the lamellar cross-section is perpendicular to the observed surface) was selected. The selected image was converted to the frequency domain using a fast Fourier transform ("FFT"), and the brightest region (the most common frequency component) was selected, followed by an inverse FFT. This produced an image showing the lamellar phase (e.g., Ni is black and Ru is white). A line was drawn across the lamellae to convert the contrast difference into a contrast spectrum, and this data was then loaded into Matlab. The code then locates the Ru lamellar interfaces and calculates the spacing between them. Tables 1 and 2 demonstrate the significant effect of adding a third element on the workability and age-hardenability of Ni-Ru ternary and higher alloys.
[0063] Binary Ni-Ru compositions were synthesized over a range of Ru concentrations. The binary alloys were designated alloys 2147 (28.8 wt.% Ru), 2179 (34.6 wt.% Ru), 2148 (40.1 wt.% Ru), and 2293 (44.8 wt.% Ru). Each sample was homogenized at 1,400 °C under a weakly reducing N2-3.5% H2 atmosphere (except alloy 2293, which was homogenized at 1,500 °C). Afterward, some samples retained coarse, insoluble Ru particles. The compositions were successfully subjected to cold area reduction after the homogenization heat treatment, demonstrating their processability. For the low-Ru binary composition CE-1 (10.0 wt.% Ru), no decomposition was achieved even with extended age-hardening heat treatment at 700 °C.
[0064] The effects of ternary and higher element additions on the workability and age-hardenability of Ni-Ru ternary and higher alloy substrates were significant. With regard to platinum, the nickel-ruthenium-platinum alloys investigated were found to be workable. Increasing platinum additions caused a delay in the discontinuous precipitation reaction. Alloy 2180, which contained 5.3 wt.% Pt in a nickel-ruthenium matrix, completely dissolved during the 700°C age-hardening process. In contrast, higher platinum concentrations, such as 15 wt.% in Alloy 2182, inhibited the age-hardening reaction, such that approximately half of the alloy remained as an undissolved solid solution after the same age-hardening heat treatment.
[0065] Rhenium has low solubility in nickel and a high affinity for ruthenium. While they remain processable, the addition of rhenium to Ni-Ru ternary and higher alloys in alloys 2183 and 2184 resulted in a large amount of insoluble primary ruthenium-rich particles throughout the sample. These primary particles may be effective in reducing the volume fraction of lamellar microstructures by reducing the proportion of ruthenium available to participate in the DP reaction and promoting decoupled DP. In an attempt to homogenize nickel-ruthenium-rhenium alloy compositions, an additional composition, alloy 2217, was synthesized with a higher ratio of nickel to ruthenium. Despite the relatively low ruthenium concentration in alloy 2217, a large amount of ruthenium-rich particles remained after homogenization at 1,400 °C.
[0066] Ternary alloying additions of tungsten (Alloy 2186), molybdenum (Alloy 2188), tantalum (Alloy 2191), and niobium (Alloy 2192) also effectively inhibited colony growth, and these samples did not completely decompose at 700°C. Preventing decomposition did not provide any benefit in refining the mean lamellar wavelength. Low concentrations of niobium in Alloy 2225 were also found to reduce the alloy's castability and introduce porosity that hinders processing. It is believed that Ni-Ru ternary and higher alloys containing at least one of tungsten, molybdenum, tantalum, and niobium may still be feasible with different melting points and casting methods, as well as different alloy compositions.
[0067] In alloy 2189, the addition of palladium to a nickel-ruthenium matrix was found to induce non-equilibrium melting in the alloy during homogenization heat treatment at 1,400°C. The pronounced grain boundary decoration with a palladium-nickel pseudoeutectic phase and abundant porosity is believed to result from grain boundary liquation. It is currently believed that nickel-ruthenium-palladium alloys may still be feasible with different homogenization heat treatment practices and different alloy compositions.
[0068] In alloy 2190, the addition of rhodium allowed rapid colony growth during discontinuous precipitation. This composition completely decomposed at 700°C, with fine lamellar regions separated by coarse lamellae and equiaxed grains. The rhodium solute appeared to have little effect on changing the average lamellar wavelength.
[0069] Gold was found to be an effective refiner of the lamellar structure; it increased the reaction front velocity and created heterogeneous nucleation sites within the alloy particles. A range of nickel:ruthenium:gold ratios was synthesized, and all were found to be processable. Compositions with lower nickel concentrations tended to retain higher volume fractions of ruthenium-rich and gold-rich minor components. Although some gold- and ruthenium-saturated alloys contained phases that were insoluble upon homogenization at 1,400°C, the synthesized samples remained processable. Age-hardening at approximately 700°C was observed to promote the formation of a fine lamellar structure. The reason why gold drives rapid decomposition is unclear; it may be due to the high solubility and mutual immiscibility of ruthenium and gold in nickel, the tendency of nickel and gold to undergo spinodal decomposition, the creation of additional heterogeneous nucleation sites, and / or increased interfacial diffusivity. The only exception to the age hardenability was alloy 2288, where the high gold content of 20.3 wt% resulted in gold-rich grain boundary decoration that apparently interfered with DP. Alloy 2288 instead developed a Widmanstätten morphology after prolonged age hardening.
[0070] Cobalt and iridium have high solubility in both nickel and ruthenium. Low-cobalt (Alloy 2187), high-cobalt (Alloy 2218), and iridium (Alloy 2219) alloying additions in a nickel-ruthenium matrix resulted in alloys homogenized into a single-phase solid solution without ruthenium release or precipitate formation. The alloys were processable. The aged microstructures of both compositions were comparable to that of the nickel-ruthenium binary Alloy 2148. Alloy 2218 was observed to form a thick blue oxide layer when heat-treated in open atmosphere and was magnetic after age hardening.
[0071] The addition of chromium to a nickel-ruthenium matrix to synthesize alloy 2220 was observed to coarsen the dendritic ruthenium-rich regions in the as-cast microstructure into a mesoscale dual-phase microstructure. Chromium distribution measured by energy-dispersive X-ray spectroscopy showed a nearly uniform partitioning between the nickel-rich (suspected face-centered cubic) and ruthenium-rich (suspected hexagonal close-packed) phases. Aging at 700°C resulted in only partial decomposition. It is currently believed that different homogenization treatments and alloy compositions can result in a finer dual-phase structure, which will lead to finer microstructures and an increased population of heterogeneous nucleation sites for DP.
[0072] Alloy 2221 contained added vanadium. After homogenization at 1,400°C, some melting was observed, indicating non-equilibrium melting. The alloy containing 7.4 wt% vanadium remained workable, and the normal DP age-hardening response was observed.
[0073] The addition of copper to the nickel-ruthenium matrix also caused ruthenium removal from the nickel matrix, subsequently agglomerating into coarse particles when Alloy 2223 was homogenized, although the composition remained workable. The copper solute was observed to refine the lamellar structure after age-hardening heat treatment.
[0074] The addition of zirconium to a nickel-ruthenium matrix resulted in significant melting after homogenization at 1,400°C. After resolidification, zirconium-rich precipitates formed in both the nickel matrix and the ruthenium particles. As a result, Alloy 2222 was unworkable. Alloy 2224, an alloyed addition of titanium to a nickel-ruthenium matrix, was observed to be unprocessable. Low-melting eutectic trace elements appeared during homogenization at 1,400°C, and titanium caused significant oxidation on the exterior of the experimental specimens. Alloy 2226, containing 12.9 wt.% iron, was found to lower the liquidus temperature of the Ni matrix below 1,400°C. Full ingot homogenization could not be completed, and aging hardness could not be evaluated; therefore, the iron-containing compositions were unworkable. It is noted that the nickel-ruthenium ternary or higher alloys disclosed herein may include at least one of titanium, zirconium, or iron, for example, when the nickel-ruthenium ternary or higher alloy includes certain ternary or higher addition elements and / or exhibits certain compositions.
[0075] As discussed above, the hardness of Ni—Ru ternary or higher alloys was measured after homogenization. Table 2 shows the hardness of various alloys after homogenization. Figure 8A is a graph showing the hardness of various Ni—Ru binary alloys to determine the effect of ruthenium on a homogenized nickel-rich matrix. As shown in Figure 8A, the Ni—Ru binary alloys are significantly harder than pure unstrained nickel, with hardnesses of approximately 100 HK, demonstrating that solid solution strengthening is proportional to the level of ruthenium in the Ni—Ru binary alloy. Figure 8B is a graph showing the hardness of various Ni—Ru binary alloys, as well as the Ni—Ru ternary or higher alloys of the present disclosure, after homogenization. Unexpectedly, the post-homogenization hardness did not change from binary Ni—Ru alloy 2148, even at higher concentrations of the ternary solute. Alloy 2220 (Ni-Ru-Cr) exhibits a high hardness region of about HK 610, which corresponds to the retention of a presumed Ru-rich hexagonal close-packed phase.
[0076] In the examples, it was demonstrated that at least some Ni-Ru ternary or higher alloys exhibited DP behavior during age-hardening treatment. For example, Figures 9A-9D show images obtained from alloy 2236 (Ni-Ru-Au) (Figure 9A), alloy 2148 (Ni-Ru) (Figure 9B), alloy 2179 (Ni-Ru) (Figure 9C), and alloy 2147 (Ni-Ru) (Figure 9D), respectively, showing the various wavelengths of their discontinuously precipitated fine components. Note that Figures 9A-9D are arranged from the finest average lamellar wavelength (Figure 9A) to the coarsest average lamellar wavelength (Figure 9D). Note that alloy 2236 and alloy 2148 in the images of Figures 9A-9D were decomposed at 700°C, alloy 2179 was decomposed at 850°C, and alloy 2147 was decomposed at 1000°C.
[0077] Figure 10 is a graph showing the relationship between the measured hardness of various Ni-Ru binary and higher alloys after age hardening and the measured mean lamellar wavelength obtained from Table 2 (Figures 7A and 7B). Figure 10 shows the dependence of hardness on mean lamellar wavelength. The very fine microstructural features are believed to drive the age hardening characteristics to extreme hardnesses above 500 HK. When examined in log-log format, this relationship becomes linear, suggesting a power-law relationship similar to Hall-Petch between hardness and mean lamellar wavelength. Therefore, further optimization to refine the mean lamellar wavelength is expected to increase alloy hardness.
[0078] As discussed previously, it has also been found that aging Ni-Ru ternary or higher alloys below the nickel-ruthenium solvus temperature does not in itself guarantee decomposition. For example, after long-term aging of alloy 2179 at 1150°C, very few DP nuclei were observed. The hindered transformation is most likely due to the difficulty of heterogeneous nucleation at high temperatures. It is also possible to achieve complete decomposition below 700°C, as demonstrated by alloys 2236 and 2293. Higher additions of Au and Ru can result in faster reaction front propagation at lower temperatures, resulting in fine decomposition at 600°C.
[0079] Figure 11 is a ternary phase diagram showing the hardness of Ni-Ru-Au alloys at HK. Visualization of the age-hardening results in the nickel-ruthenium-gold ternary alloy space shows that increasing the ruthenium and gold concentrations have an unexpected synergistic effect in increasing the age-hardened hardness. Figure 11 illustrates this synergistic effect, with the hardness lines bunched together near the 0 wt. % gold axis, indicating that a small increase in the gold content of the Ni-Ru alloy significantly increases the alloy's age-hardened microhardness.
[0080] Figure 12 is a graph showing the effect of adding a tertiary element, gold, to a nickel-ruthenium matrix after age hardening. Figure 12 also shows that increasing the concentrations of ruthenium and gold has an unexpected synergistic effect on increasing the age-hardened hardness. For example, for alloys based on Alloy 2147 and Alloy 2179, Figure 12 shows that increasing the amount of gold in the Ni-Ru alloy from 0 wt. % (i.e., absent) to 0.08 wt. % increases the age-hardened microhardness of the Ni-Ru alloy by approximately 10%, and that increasing the amount of gold in the Ni-Ru alloy from 0.08 wt. % to 0.3 wt. % also has a significant effect on the age-hardened microhardness of the Ni-Ru ternary alloy. Similarly, for alloys based on Alloy 2148, Figure 12 demonstrates that increasing the amount of gold in the Ni-Ru alloy from 0 wt. % to 0.1 wt. % and from 0.1 wt. % to 0.3 wt. % significantly increases the age-hardened microhardness of the Ni-Ru ternary alloy. It was unexpected that gold would have a significant effect on the age-hardened microhardness of Ni-Ru ternary or higher alloys at such low concentrations. Copper was found to have a similar effect on the age-hardened microhardness of the Ni-Ru ternary or higher alloys disclosed herein. It should be noted that the other ternary or higher alloying elements disclosed herein, even at low concentrations, may have a similar effect as gold on the microhardness of Ni-Ru ternary or higher alloys, or other significant effects on the properties of Ni-Ru ternary or higher alloys.
[0081] The trend lines added to Figure 12 (estimating the relationship between age-hardened microhardness and gold concentration for each alloy) flatten out above a threshold, indicating that increasing the gold concentration in the Ni-Ru ternary alloy above a threshold (e.g., about 4 wt%) has minimal effect on the microhardness of the Ni matrix. Without wishing to be bound by theory, it is believed that the trend lines flatten out because the additional gold moves the bulk alloy composition into the two- and three-phase region. The additional gold does not mix into the Ni matrix, but forms a distinct Au-Ni phase, and depending on the composition, the Ru-Ni phase is stable along with the Au-Ni phase and the Ni matrix. While the bulk composition changes phase fraction, the composition of the constituent phases remains constant. Furthermore, without wishing to be bound by any particular theory, it is believed that the addition of gold no longer affects the lamellar length scale and microhardness of the Ni matrix, but that modifying the manufacturing process used to form the Ni-Ru ternary or higher alloy, changing the ruthenium concentration in the Ni-Ru ternary or higher alloy, or including additional ternary or higher alloys in the Ni-Ru ternary or higher alloy may significantly affect the overall hardness and electrical conductivity of the Ni-Ru ternary, even when the gold concentration is increased above a threshold value.
[0082] Among the Ni-Ru-Au compositions, alloys 2236 and 2246 unexpectedly exhibited high hardness. Alloy 2236 has a lower Au concentration and a higher Ru concentration, producing a harder material. This material exceeds the requirements for pogo pin applications. Alloy 2246 meets the nominal hardness target and contains less Ru. This allows the alloy to be more easily forged, opening up the possibility of using lower temperatures for homogenization.
[0083] It is also possible to achieve complete decomposition below 700°C, as demonstrated by alloy 2236. Higher concentrations of Au result in faster reaction front propagation at lower temperatures, allowing for fine decomposition at 600°C.
[0084] While various aspects and embodiments have been disclosed herein, other aspects and embodiments are contemplated. The various aspects and embodiments disclosed herein are for purposes of illustration and are not intended to be limiting.
[0085] Terms of degree (e.g., "about," "substantially," "generally," etc.) indicate structurally or functionally insignificant variations. In one example, when a term of degree includes a term indicating a quantity, the term of degree is interpreted to mean ±10%, ±5%, or +2% of the term indicating a quantity. In one example, when a term of degree is used to modify a shape, the term of degree indicates that the shape modified by the term of degree has the appearance of the disclosed shape. For example, the term of degree may be used to indicate that a shape may have rounded corners instead of sharp corners, curved edges instead of straight edges, one or more protrusions extending therefrom, an oval shape, the same shape as the disclosed shape, etc.
Claims
1. A nickel and ruthenium based alloy comprising: about 48% to about 71% nickel, by weight of said alloy; about 17% to about 45% ruthenium by weight of the alloy; and at least one ternary or higher addition comprising gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, tungsten, or any combination thereof, from greater than 0% to about 20% by weight of the alloy; Alloys containing
2. 10. The alloy of claim 1, wherein nickel is present in an amount between about 54% and about 71% by weight of the alloy.
3. 10. The alloy of claim 1, wherein nickel is present in an amount of about 50% to about 60% by weight of the alloy.
4. 10. The alloy of claim 1, wherein ruthenium is present in an amount between about 27% and about 45% by weight of the alloy.
5. The alloy of claim 1, wherein ruthenium is present in an amount of about 25% to about 40% by weight of the alloy.
6. 10. The alloy of claim 1, wherein said at least one ternary or higher addition element is present in an amount from about 0.1% to about 6% by weight of said alloy.
7. 10. The alloy of claim 1, wherein the at least one ternary or higher addition element is present in an amount ranging from about 0.7% to about 11% by weight of the alloy.
8. 10. The alloy of claim 1, wherein said at least one ternary or higher addition element is present in an amount ranging from about 1.4% to about 15% by weight of said alloy.
9. 10. The alloy of claim 1, wherein said at least one ternary or higher addition comprises gold.
10. 10. The alloy of claim 1, wherein the alloy is age hardened.
11. 11. The alloy of claim 10, wherein the alloy exhibits a Knoop microhardness of about 500 or greater.
12. 11. The alloy of claim 10, wherein the alloy exhibits a Knoop microhardness of about 600 or greater.
13. 10. The alloy of claim 1, wherein the alloy exhibits a mean lamellar wavelength of less than or equal to about 150 nm.
14. A test probe or test probe component comprising the nickel-ruthenium based alloy of claim 1.
15. 15. The test probe or test probe component of claim 14, wherein the probe is configured as a cobra probe, a cantilever probe, a pogo pin probe, an LED probe, a vertical probe, or a MEMS probe.
16. A probe card comprising the test probe or test probe component of claim 14.
17. 1. A method of making a nickel-ruthenium based alloy, comprising forming an alloy, the alloy comprising: about 48% to about 71% nickel, by weight of said alloy; about 17% to about 45% ruthenium by weight of the alloy; and at least one ternary or higher addition comprising gold, cobalt, chromium, copper, iridium, molybdenum, niobium, palladium, platinum, rhenium, rhodium, tantalum, vanadium, tungsten, or any combination thereof, from greater than 0% to about 20% by weight of the alloy; The method of claim 1, wherein the alloy comprises
18. 18. The method of claim 17, further comprising homogenizing the alloy after forming the alloy.
19. 18. The method of claim 17, further comprising age hardening the alloy at a temperature of about 600°C to about 1,300°C.
20. 20. The method of claim 19, further comprising forming the alloy into a desired shape before age hardening the alloy.
21. The method of claim 17, further comprising age hardening the alloy at a temperature of about 700°C to about 850°C.